Challenges and Opportunities for Physical Activity Interventions in Type 2 Diabetes Mellitus sufferers in Indigenous Areas throughout the world: A Scoping Review - Sulfikar, Andi (Jambura Nursing Journal, 2024)
Introduction: Physical activity interventions play a crucial role in managing Type 2 Diabetes Mellitus (T2DM) in Indigenous populations. However, there are significant challenges in implementing these interventions in Indigenous areas, including limited access to facilities, cultural barriers, and environmental factors. Objective: This scoping review aimed to identify and summarize the challenges and opportunities for physical activity interventions in Indigenous areas for individuals with T2DM. Method: This scoping review utilized a comprehensive search strategy to identify relevant literature from various electronic databases. The literature search was focused on studies that explored physical activity interventions in Indigenous populations with Type 2 Diabetes Mellitus. Result: The search strategy resulted in the identification of several studies that highlighted the challenges and opportunities for physical activity interventions in Indigenous areas for individuals with Type 2 Diabetes Mellitus. Numerous challenges were identified, including limited access to recreational facilities, cultural barriers, and environmental factors. Limited access to recreational facilities was one of the key challenges identified in the literature. Conclusion: The challenges faced in implementing physical activity interventions in Indigenous areas for individuals with T2DM are significant, particularly limited access to recreational facilities, cultural barriers, and environmental factors. However, there are also opportunities for addressing these challenges and improving physical activity interventions in Indigenous areas for individuals with T2DM. One opportunity is the incorporation of cultural aspects into physical activity interventions, such as traditional Indigenous physical activities. Keywords: challenges, Indigenous areas, opportunities, physical activity interventions, Type 2 Diabetes Mellitus.